2014
DOI: 10.1111/adj.12213
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and antibiotic resistant bacteria isolated from primary dentition infections

Abstract: Background: Bacterial resistance to antibiotics is a health problem in many parts of the world. The aim of this study was to identify bacteria from dental infections and determine bacterial resistance to antibiotics used in dental care in the primary dentition. Methods: This cross-sectional study comprised 60 children who presented for dental treatment for active dental infections in the primary dentition. Samples from dental infections were collected and bacteria were identified by polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Previous studies have reported resistance to commonly used antibiotics in high proportion of oral E. faecalis strains isolated from patients with apical periodontitis [30,31]. The rapid emergence of antimicrobial resistance among enterococci makes it difficult to treat chronic infections, different aerobic and anaerobic bacterial species are antibiotic resistant especially in refractory endodontic infections where E. faecalis is involved [17]. Thus, the eradication and prevention of reinfection of E. faecalis during periapical surgery or in the treatment of endodontic refractory infections are important issues for clinical success.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported resistance to commonly used antibiotics in high proportion of oral E. faecalis strains isolated from patients with apical periodontitis [30,31]. The rapid emergence of antimicrobial resistance among enterococci makes it difficult to treat chronic infections, different aerobic and anaerobic bacterial species are antibiotic resistant especially in refractory endodontic infections where E. faecalis is involved [17]. Thus, the eradication and prevention of reinfection of E. faecalis during periapical surgery or in the treatment of endodontic refractory infections are important issues for clinical success.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to emphasize that Cs NPs concentrations were lower (0.012%-0.0015%) than those used with chlorhexidine (0.08%-0.01%). The method used to count CFUs in this study has been previously reported [17] and is an estimate of the number of cells able to form colonies under the conditions on agar plates. Even though this method has limitations, it offers several advantages compared with inhibition halos as these are more susceptible to bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another aspect to be considered is the oral biofilm, which includes several bacterial species and has a structure that depends on the patient's age, dentition type, and systemic medical condition(s) . Furthermore, the biofilm's morphological structure varies from case to case, but a unique pattern for active dental infections has not been identified …”
Section: American Heart Association Guidelines For Antibiotic Prophylmentioning
confidence: 99%
“…The treatment of periodontal disease consists in both surgical (gum surgery and bone grafts) and non-surgical approaches (removal of the microbial plaque and administration of antibiotics). Identification of pathogenic species of bacteria is essential for the antibiotic treatment (Loloya- Rodriguez et al, 2014). In addition, quantifying the bacterial load can help monitoring the progression of the treatment.…”
Section: Introductionmentioning
confidence: 99%